100 ASYMPTOMATIC PEPTIC ULCER PERFORATION IN AN 82-YEAR-OLD. Issue 1 (1st January 2007) - Sircar, P.; Godkar, D.; Naaz, N.; Niranjan, S.; Yakoby, M.
Abstract : Introduction: Peptic ulcer perforation is rarely missed in clinical practice because of its dramatic presentation. Even though a significant proportion of peptic ulcers may be asymptomatic, peptic perforation is rarely ever silent. Although the pathogenesis of ulcer pain is largely unclear, it has been postulated that most patients develop symptoms when acid bathes ulcer craters. The sudden development of severe, diffuse abdominal pain in a patient with preexisting ulcer disease may indicate perforation. We describe below an unusual case of asymptomatic duodenal perforation. Case Report: A 82-year-old lady was admitted to the hospital with bilateral leg swelling. A Doppler study of the lower extremities revealed acute deep vein thrombosis in the left popliteal vein. The patient was started on anticoagulation with enoxaparin and warfarin. Surprisingly, her prothrombin time done after 2 days of prescribing warfarin at 5 mg/d shot up to > 60 seconds. At that time, effort was made to rule out any major bleeding secondary to coagulopathy, and CT scans of the abdomen and pelvis were done. The study showed no evidence of intraperitoneal bleed but revealed small amounts of free air around the liver and ligamentum teres, with minimal amount of free fluid draining along the paracolic gutter. The patient, however, had no gastrointestinal symptoms and displayed no peritoneal signs, such as rebound tenderness or rigidity. However, in view of significant radiologic findings, the patient underwent exploratory laparotomy, and she was found to have a 7 to 8 mm perforation in the first part of the duodenum with natural omental sealing, which was successfully closed. The patient did well subsequently and was discharged home. Discussion: This case raises many questions for clinicians. Is there such an entity as chronic duodenal perforation? If so, what categories of patients are prone to develop them? Can there be any screening methodology for asymptomatic duodenal perforations, or is there any utility in doing so? Does coagulopathy predispose the patient to ulcer perforation? Indeed, it is possible that certain patients may have microperforations that nature seals by itself with omental patching without causing major repercussions in terms of peritonitis and death. Certainly, more research is necessary to answer these questions; until then it may not be possible for surgeons to defer or decide against operating on asymptomatic peptic perforations, until classic symptoms develop.